2020
DOI: 10.18632/aging.103033
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine palmitoyltransferase 1C contributes to progressive cellular senescence

Abstract: Stable transfection manipulation with antibiotic selection and passaging induces progressive cellular senescence phenotypes. However, the underlying mechanisms remain poorly understood. This study demonstrated that stable transfection of the empty vector induced PANC-1 cells into cellular senescence. Metabolomics revealed several acylcarnitines and their upstream regulatory gene, carnitine palmitoyltransferase 1C (CPT1C) involved in fatty acid β-oxidation in mitochondria, were strikingly decreased in senescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Besides, the knockdown of CPT1C inhibited the growth and tumorigenesis of PC [198]. Regarding the role of cell death related to lipid catabolism, targeting ferroptosis may be another attractive treatment for cancer.…”
Section: Targeting Lipid Catabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the knockdown of CPT1C inhibited the growth and tumorigenesis of PC [198]. Regarding the role of cell death related to lipid catabolism, targeting ferroptosis may be another attractive treatment for cancer.…”
Section: Targeting Lipid Catabolismmentioning
confidence: 99%
“…At the molecular level, it has been observed that CPT1A and CPT1B levels are higher in drug‐resistant pancreatic CSCs, and the oxidative phosphorylation in drug‐resistant cells was due to FAO [ 195 ]. Knockdown of CPT1C inhibited the tumorigenesis of PANC‐1 cells in vivo and further suppressed xenograft tumor growth in situ [ 198 ]. In conclusion, the dynamic FAO regulation exerts a critical role in cancer progression, and targeting the FAO signaling pathway might be a promising therapeutic strategy for PC.…”
Section: Alterations Of Lipid Metabolism In Pcmentioning
confidence: 99%
“…Mitophagy is activated in senescent cells [36]. Mitochondrial depolarization is a hallmark of mitophagy [37].…”
Section: Extraction and Culture Of Foreskin Fibroblastsmentioning
confidence: 99%
“…The involvement of carnitine palmitoyltransferase 1C (CPT1C) in the mitochondrial β-oxidation of fatty acids is important for cell survival. Low activity of CPT1C results in a negative cellular outcome with increased metabolic and oxidative stress, decreased cell growth, and dysregulated mitochondria [157]. Increasing the expression and activity of CPT1C reverses the negative cellular effects.…”
Section: Involvement Of Metabolic Stress In Pdacmentioning
confidence: 99%